Development of a Coloring Book as an Educational Medium on Animal-Based Protein Foods for Students at SD Negeri 2 Lamcot, Darul Imarah District, Aceh Besar Regency - Fatmawati Malani. HS; Arnisam Arnisam (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2026)
Poor oral and dental health can impair food intake by causing pain and difficulty chewing, leading to inadequate nutrient consumption and increasing the risk of malnutrition in children. Inadequate nutrition knowledge is one of the factors contributing to poor dietary habits among school-aged children. Nutrition education using engaging learning media may improve children's understanding of healthy food choices. This study aimed to develop and evaluate a coloring book on animal protein sources as a nutrition education medium for elementary school children. This study employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The coloring book was validated by experts in content, media, and language and tested among 30 elementary school students. Data were collected using validation and knowledge questionnaires and analyzed using a paired-samples t-test. The validation results demonstrated that the coloring book was highly feasible, with average scores of 92.77% from content experts, 90.76% from media experts, and 90.00% from language experts. Students also rated the coloring book as easy to understand. The mean knowledge score increased significantly from 11.17 before the intervention to 15.90 after the intervention (p < 0.001). These findings indicate that the coloring book is a valid and feasible educational medium that effectively improves elementary school children's knowledge of animal protein sources and has the potential to support nutrition education programs in primary schools.